1993
DOI: 10.1080/15287399309531729
|View full text |Cite
|
Sign up to set email alerts
|

Effects on thyroid hormone metabolism and depletion of lung vitamin a in rats by airborne particulate matter

Abstract: Thyroxine (T4) and vitamin A are important regulators of normal epithelial differentiation and proliferation and might act in the promotion phase of carcinogenesis. Thyroid hormone and vitamin A metabolism are linked by a common plasma carrier protein, transthyretin (TTR). Polychlorinated biphenyls (PCBs) and related organochlorine compounds deplete vitamin A and thyroxine by interaction with TTR and alteration of their metabolism in hepatic and other organs. In the present report an outdoor airborne particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In this regard, thyroid hormone and vitamin A metabolism are linked by a com-mon plasma carrier protein, transthyretin (TTR). Polychlorinated biphenyls and related organochlorine compounds deplete vitamin A and thyroxine by interaction with TTR and by alteration of their metabolism in the liver and other organs (Heussen et al, 1993). However, altered differentiation of vitamin A-sensitive epithelia or thyroid or estrogen hormone-sensitive epithelia has not been examined in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, thyroid hormone and vitamin A metabolism are linked by a com-mon plasma carrier protein, transthyretin (TTR). Polychlorinated biphenyls and related organochlorine compounds deplete vitamin A and thyroxine by interaction with TTR and by alteration of their metabolism in the liver and other organs (Heussen et al, 1993). However, altered differentiation of vitamin A-sensitive epithelia or thyroid or estrogen hormone-sensitive epithelia has not been examined in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinogenic compounds can cause irritation and inflammation at sites of exposure and are often antigenic (251)(252)(253)(254)(255)(256)(257)(258)(259). Respiratory carcinogens (or suspected carcinogens) include antimony compounds (260)(261)(262)(263), arsenic compounds (263)(264)(265)(266)(267)(268), hexamethylphosphoramide (269,270), 4,4´-methylene-bis(2-chloroaniline) (271,272), bromoform (273,274), methylene chloride (275), 4,4´-methylenedianiline (276,277), nitrobenzene (mice) (278-280), 4-nitrobiphenyl (281), 2-nitropropane (282)(283)(284)(285), N-nitroso-Nmethylurea (286), N-nitrosodimethylamine (287)(288)(289)(290), N-nitrosomorpholine (291-293), pentachlorophenol (mice) (294,295), polycyclic aromatic hydrocarbons (250,254,255), 1,3-propane sultone (296,297), propylene oxide (298-300), 2,3,7,8-tetrachlorodibenzop-dioxin (TCDD) (301-305), 2,4-toluene diamine (306,307), viny...…”
Section: Evaluating Human Exposure and Its Relationship To Asthmamentioning
confidence: 99%
“…It is possible that this mechanism may result in an initial accumulation of vitamin A prior to depletion of stores, offering a potential explanation for the apparent paradoxical result. Increased vitamin A levels due to contaminants have been reported in other species (Heussen et al, 1993). In addition, this may provide an explanation for the significant nonlinear relationship between vitamin A concentration and total OC compounds level, whereby there was an initial increase in vitamin A as the OC compound burden increased, followed by a decline as OC compound levels increased further (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…However, in studies with redeared sliders (Trachemys scripta), o,p9-DDT was found to have higher estrogenic activity than DDT (Sparling et al, 2000). O,p9-DDT is a metabolite of DDT, and some OC compounds are known require metabolization before they are able to interfere with receptor binding (Heussen et al, 1993). Furthermore, even structurally related compounds may have different degrees of biologic activity (Guillette et al, 1995).…”
Section: Resultsmentioning
confidence: 99%